Methylene Blue Mitigates Acute Neuroinflammation after Spinal Cord Injury through Inhibiting NLRP3 Inflammasome Activation in Microglia - Lin, Zhi-Hang; Wang, Si-Yuan; Chen, Li-Li; Zhuang, Jia-Yuan; Ke, Qing-Feng; Xiao, Dan-Rui; Lin, Wen-Ping (Frontiers in Cellular Neuroscience, 2017)
The spinal cord injury (SCI) is a detrimental neurological disease involving the primary mechanical injury and secondary inflammatory damage. Curtailing the detrimental neuroinflammation would be beneficial for spinal cord function recovery. Microglia reside in the spinal cord and actively participate in the onset, progression and perhaps resolution of post-SCI neuroinflammation. In the current study, we tested the effects of methylene blue on microglia both in vitro and in a rat SCI model. We found that methylene blue inhibited the protein levels of IL-1β and IL-18 rather than their mRNA levels in activated microglia. Further investigation indicated that methylene blue deceased the activation of NLRP3 inflammasome and NLRC4 inflammasome in microglia in vitro. Moreover, in the rat SCI model, the similar effect of methylene blue on post-SCI microglia was also observed, except that the activation of NLRC4 inflammasome was not seen. The inhibition of microglia NLRP3 inflammasome was associated with down-regulation of intracellular reactive oxygen species. The administration of methylene blue mitigated the overall post-SCI neuroinflammation, demonstrated by decreased pro-inflammatory cytokine production and leukocyte infiltrates. Consequently, the neuronal apoptosis was partially inhibited and the hind limb locomotor function was ameliorated by methylene blue treatment. Our research highlights the role of methylene blue in inhibiting post-SCI neuroinflammation, and suggests that methylene blue might be used for SCI therapy.